Powder material for three-dimensional molding, method for producing three-dimensional molded article, and three-dimensional molded article

By using a three-dimensional molding powder material containing homopolypropylene, nanofibers and block polypropylene, combined with a laser sintered 3D printer, the problem of difficult to produce a polypropylene molded body with excellent impact resistance and bending characteristics in the prior art is solved, and efficient characteristic balance and performance improvement are achieved.

CN119907827APending Publication Date: 2025-04-29KYOTO UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380070258.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-04
Filing Date
2023-10-02
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult to manufacture a polypropylene molded body with excellent balance of impact resistance and bending characteristics through a 3D printer.

Method used

The powder material for three-dimensional molding of the first resin powder containing homopolypropylene and nanofibers and the second resin powder containing block polypropylene is used to perform three-dimensional molding by a laser sintering 3D printer.

Benefits of technology

The excellent balance between impact resistance and bending characteristics is achieved, and the Sharpi impact strength and bending elastic modulus of the three-dimensional shape are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907827A_ABST
    Figure CN119907827A_ABST
Patent Text Reader

Abstract

A powder material for three-dimensional molding according to the present invention contains a first resin powder containing homo-polypropylene and nanofibers and a second resin powder containing block polypropylene. Examples of nanofibers are cellulose nanofibers (CNF). The block polypropylene comprises, for example, a propylene-olefin copolymer (the olefin does not include propylene). The powder material is suitable for manufacturing a polypropylene molded body having an excellent balance between impact resistance and bending characteristics by using a 3D printer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder material for three-dimensional modeling, a method for producing a three-dimensional modeling object, and a three-dimensional modeling object. Background Art

[0002] Polypropylene is a resin material that has excellent moldability and excellent bending properties while being lightweight. In view of the above characteristics, the use of polypropylene in vehicle components, typically interior decorative components, bumpers and other exterior decorative components, is also increasing. Polypropylene molded bodies for vehicles are usually manufactured by injection molding. Injection molding can produce molded bodies with curved surfaces. Patent Document 1 discloses a resin composition containing polypropylene that is optimized for injection molding.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-12718

[0006] Problems to be solved by the invention

[0007] For vehicle components, an excellent balance between impact resistance and bending properties is required. In recent years, the manufacture of vehicle components using 3D printers has attracted attention for the purpose of manufacturing without using molds and manufacturing components with complex shapes. However, there has been insufficient research on the use of 3D printers to manufacture the above-mentioned well-balanced polypropylene molded bodies. According to the research of the present inventors, it is difficult to achieve an excellent balance of properties when a powder material containing homopolypropylene as a standard polypropylene is applied to a 3D printer as a resin material. In view of the above situation, an object of the present invention is to provide a powder material for three-dimensional modeling suitable for manufacturing polypropylene molded bodies with an excellent balance between impact resistance and bending properties using a 3D printer.

[0008] Means for solving problems

[0009] The present invention provides a powder material for three-dimensional modeling, which contains:

[0010] A first resin powder comprising homopolypropylene and nanofibers, and

[0011] A second resin powder comprising block polypropylene.

[0012] From another aspect, the present invention provides a method for manufacturing a three-dimensional object.

[0013] The three-dimensional modeling powder material of the present invention is three-dimensionally molded using a laser sintering 3D printer to obtain a three-dimensional modeled object.

[0014] From another aspect, the present invention provides a three-dimensional object.

[0015] It is a three-dimensional object made of polypropylene.

[0016] The three-dimensional structure has a first domain including homopolypropylene and nanofibers and a second domain including block polypropylene.

[0017] Effects of the Invention

[0018] The powder material for three-dimensional modeling of the present invention is suitable for producing a polypropylene molded body having an excellent balance between impact resistance and bending properties using a 3D printer. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram showing an example of the powder material of the present invention.

[0020] Figure 2 This is a schematic diagram for explaining the process of manufacturing a three-dimensional object using a laser sintering 3D printer.

[0021] Figure 3 It is a cross-sectional view schematically showing an example of the three-dimensional modeled object of the present invention.

[0022] Figure 4 This is an enlarged observation image of the cross section of the three-dimensional modeled object produced in Example 3.

[0023] Figure 5 This is an enlarged observation image of the cross section of the three-dimensional modeled object produced in Comparative Example 1.

[0024] Figure 6 This is a graph showing the relationship between the content of block PP in the powder material used and the Charpy impact strength for each three-dimensional shaped object produced in Examples, Comparative Examples, and Reference Examples. DETAILED DESCRIPTION

[0025] The powder material for three-dimensional modeling according to the first aspect of the present invention contains:

[0026] A first resin powder comprising homopolypropylene and nanofibers, and

[0027] A second resin powder comprising block polypropylene.

[0028] In the second aspect of the present invention, for example, with respect to the powder material for three-dimensional modeling of the first aspect,

[0029] The blending ratio of the second resin powder to the first resin powder is 0.6 or more and 4.0 or less, expressed as the mass of the second resin powder when the mass of the first resin powder is set to 1.

[0030] In the third aspect of the present invention, for example, with respect to the powder material for three-dimensional modeling of the first aspect,

[0031] The blending ratio of the second resin powder to the first resin powder, expressed as the mass of the second resin powder when the mass of the first resin powder is set to 1, is 1.4 or more and 3.0 or less.

[0032] In a fourth aspect of the present invention, for example, in the three-dimensional modeling powder material of any one of the first to third aspects, the content of the nanofibers in the first resin powder is 15% by mass or less.

[0033] In a fifth aspect of the present invention, for example, in the three-dimensional modeling powder material of any one of the first to fourth aspects, the nanofibers are cellulose nanofibers.

[0034] In a sixth aspect of the present invention, for example, in the three-dimensional modeling powder material according to any one of the first to fifth aspects, the block polypropylene comprises a copolymer of propylene and an olefin, wherein the olefin does not include propylene.

[0035] The method for manufacturing a three-dimensional object according to the seventh aspect of the present invention includes the operation of three-dimensionally molding the three-dimensional modeling powder material according to any one of the first to sixth aspects using a laser sintering 3D printer to obtain a three-dimensional modeling object.

[0036] The three-dimensional shaped object according to the eighth aspect of the present invention comprises polypropylene.

[0037] It has a first phase domain including homopolypropylene and nanofibers and a second phase domain including block polypropylene.

[0038] In a ninth aspect of the present invention, for example, the three-dimensional object of the eighth aspect has a cross section where a sea-island structure is observed, and the sea-island structure has an island portion based on the first phase domain and a sea portion based on the second phase domain.

[0039] In the tenth aspect of the present invention, for example, in the three-dimensional shaped object of the eighth or ninth aspect, the unnotched Charpy impact strength based on the side impact evaluated in accordance with the provisions of JIS K7111-1:2012 is 5.5 kJ / m 2 As described above, the bending modulus evaluated according to the A method specified in JIS K7171:2016 is 1.2 GPa or more.

[0040] In the eleventh aspect of the present invention, for example, in the three-dimensional modeled object of the tenth aspect, the bending strength evaluated according to the A method specified in JIS K7171:2016 is 21 MPa or more.

[0041] [Powder materials for 3D modeling]

[0042] An example of the powder material for three-dimensional modeling of the present invention (hereinafter referred to as "powder material") is shown in Figure 1 middle. Figure 1 The powder material 1 contains a first resin powder 11 containing homopolypropylene (hereinafter referred to as homo-PP) and nanofibers, and a second resin powder 12 containing block polypropylene (hereinafter referred to as block PP). The first resin powder 11 and the second resin powder 12 are different powders from each other. By applying the powder material 1 to a 3D printer, a three-dimensional molded object as a polypropylene molded body can be manufactured. The powder material 1 is suitable for manufacturing a polypropylene molded body having an excellent balance between impact resistance and bending properties using a 3D printer. The degree of the above balance is at least higher than that of a molded body manufactured under the same manufacturing conditions using a resin powder containing homo-PP contained in the first resin powder 11. There are various types of 3D printers. The powder material 1 is particularly suitable for use in a laser sintering (SLS / SLM) 3D printer that sinters a stacked layer of a powder material using a laser.

[0043] Regarding the proportion of the second resin powder 12 relative to the first resin powder 11, it is expressed as the mass of the second resin powder 12 when the mass of the first resin powder 11 is set to 1, for example, it can be 0.6 or more and 4.0 or less. The lower limit of the ratio can also be 0.67 or more, 0.7 or more, 0.82 or more, 1.0 or more, 1.22 or more, 1.4 or more, 1.47 or more, 1.5 or more, 1.7 or more, 1.86 or more, and further 1.9 or more. The upper limit of the ratio can also be 3.5 or less, 3.0 or less, 2.7 or less, 2.3 or less, 2.2 or less, and further 2.1 or less. The upper limit and lower limit of the ratio can be arbitrarily combined. The powder material 1 whose upper limit and lower limit of the ratio are in the above range is particularly suitable for manufacturing a polypropylene molded body with excellent balance between impact resistance and bending properties. The ratio can also be 1.4 or more and 3.0 or less, and further 1.5 or more and 2.1 or less.

[0044] (First resin powder)

[0045] Homo PP is a homopolymer of propylene. The melting point of homo PP is, for example, 150 to 180°C, preferably 155 to 175°C, and more preferably 160 to 170°C. The recrystallization temperature of homo PP after melting (hereinafter referred to as recrystallization temperature) is, for example, 110 to 140°C, preferably 115 to 135°C, and more preferably 120 to 130°C. The difference between the melting point and the recrystallization temperature is preferably 30°C or more, more preferably 35°C or more, further preferably 38°C or more, and particularly preferably 40°C or more. The upper limit of the difference is, for example, 60°C or less. Resin powders having a difference between the melting point and the recrystallization temperature in the above range are particularly suitable for use in laser sintering 3D printers. The melting point and the recrystallization temperature can be evaluated by using a differential scanning calorimeter (DSC) with the heating and cooling rates set to 5°C / minute. The evaluation methods for the properties, including the melting point and the recrystallization temperature, are the same for homo PP and block PP.

[0046] Homopolymer PP is generally crystalline. The degree of crystallinity of homopolymer PP is, for example, 40 to 70%, preferably 50% or more. The degree of crystallinity can be calculated from the heat of melting (melting heat) evaluated by DSC and the theoretical melting heat of PP crystals.

[0047] The weight average molecular weight (Mw) of homopolymer PP is, for example, tens of thousands to millions, and may be 500,000 to 3,000,000, or further 500,000 to 2,000,000. Mw can be evaluated by gel permeation chromatography (GPC).

[0048] The melt flow rate (MFR) value of homopolymer PP is, for example, 5 to 60 g / 10 minutes, and may also be 20 to 60 g / 10 minutes, 30 to 50 g / 10 minutes, and further 35 to 45 g / 10 minutes. The MFR value can be measured according to the method specified in Japanese Industrial Standard (hereinafter referred to as JIS) K7210-1. The measurement temperature is set to 190°C and the load is set to 2.16 kg.

[0049] The first resin powder 11 may contain one or two or more homopolymer PPs.

[0050] The nanofibers can function as a reinforcing material that improves the bending properties of a polypropylene molded body. The nanofibers in the first resin powder 11 are typically dispersed in the homo-PP.

[0051] Nanofibers are fibrous substances that usually have an average fiber diameter of 10 μm or less. The upper limit of the average fiber diameter may also be 5 μm or less, 3 μm or less, 1 μm or less, less than 1 μm, 500 nm or less, 250 nm or less, 100 nm or less, 80 nm or less, 60 nm or less, or 40 nm or less. The lower limit of the average fiber diameter is, for example, 1 nm or more, 5 nm or more, or 10 nm or more. The average fiber length of nanofibers is, for example, 5 to 1000 μm, 5 to 500 μm, 5 to 250 μm, or 5 to 100 μm.

[0052] Examples of nanofibers are cellulose nanofibers (hereinafter referred to as CNF), cellulose nanocrystals, chitin nanofibers, chitosan nanofibers, and carbon nanotubes. However, nanofibers are not limited to the above examples. Nanofibers are preferably CNF. CNF is suitable for fusion with homopolymer PP. In addition, CNF can also act as a material that hinders the aggregation of resin powder.

[0053] The average fiber diameter of CNF is preferably 1 nm to 10 μm, more preferably 1 nm to 1 μm, and further preferably 1 nm to 500 nm. The preferred lower limit of the average fiber diameter is 3 nm or more. The fiber diameter of CNF may be uneven in the length direction of each fiber. For example, cellulose fibers having a portion with a large fiber diameter (stem portion; as an example, a diameter of 5 μm) and one or more portions with a small fiber diameter (branch portion; as an example, a diameter of about 10 nm) on the surface of the stem portion are also included in the CNF of this specification. The average fiber length of CNF is preferably 5 μm or more, more preferably 5 μm to 100 μm. CNF may contain lignin, and its hydroxyl groups may be chemically modified.

[0054] CNF can be unmodified CNF or modified CNF. An example of modified CNF is CNF whose surface is hydrophobized by modifying the hydroxyl groups of cellulose with hydrophobic groups or the like. Hydrophobized CNF is suitable for dispersion in polypropylene. Examples of modification include chemical modification such as acetyl modification and modification with alkenyl succinic anhydride (ASA). It should be noted that modification with ASA can also be applied to the continuous generation process of CNF using wood pulp as raw material.

[0055] The chemical modification of CNF in this specification means that part of the hydroxyl groups of the sugar chains and / or lignin constituting the cellulose nanomaterial (A) contained in CNF (hereinafter, the sugar chains and hydroxyl groups of lignin constituting the cellulose nanomaterial (A) are collectively referred to as the hydroxyl groups of the substance (A)) are modified by other groups. For example, CNF that has undergone at least one chemical modification selected from the following (i) to (iii) is particularly suitable for dispersion in polypropylene.

[0056] (i) A part of the hydroxyl groups of the substance (A) is esterified with a carboxylic acid represented by the following formula (1). The hydroxyl groups are converted to -O-CO-R by esterification. Esterification may be performed with two or more carboxylic acids.

[0057] R-COOH···(1)

[0058] In the formula, R represents (a) an alkyl group or an alkenyl group, (b) an alicyclic hydrocarbon group which can be cross-linked or condensed, (c) an oxyalkyl group substituted by an alicyclic hydrocarbon group which can be cross-linked or condensed, or (d) a phenoxyalkyl group, a phenoxyalkyl group substituted by an alkyl group, or a phenoxyalkyl group substituted by an alicyclic hydrocarbon group which can be cross-linked or condensed.

[0059] (ii) A part of the hydroxyl groups of the substance (A) is half-esterified with an alkyl succinic anhydride or ASA. Half-esterification means that only one carbonyl group in the alkyl succinic anhydride or ASA forms an ester bond with the hydroxyl group of the substance (A). The alkyl and alkenyl groups may be straight-chain or branched. Half-esterification may also be performed with two or more alkyl succinic anhydrides or ASA.

[0060] (iii) The hydrogen atoms of a part of the hydroxyl groups of the substance (A) are replaced by carboxymethyl, carboxyethyl, hydroxyethyl, 2-hydroxypropyl or cyanoethyl to form an ether bond. For example, when the hydrogen atoms are replaced by carboxymethyl, the hydroxyl groups are converted to -O-CH2-COOH.

[0061] When R of the carboxylic acid of formula (1) is (a) an alkyl group or an alkenyl group, the alkyl group and the alkenyl group may be straight chain or branched. The carbon number of the alkyl group and the alkenyl group is, for example, 1 to 17, or 1 to 12, 1 to 10, 1 to 6, 1 to 4, 1 to 3, 1 to 2, or 1. R is preferably an alkyl group or an alkenyl group having 1 to 17 carbon atoms, and more preferably an alkyl group having 1 to 17 carbon atoms. R is preferably a methyl group, an ethyl group, an isobutyl group, a tert-butyl group, an n-undecyl group, an n-tridecyl group, an n-pentadecyl group, or an n-heptadecyl group, and more preferably a tert-butyl group. The carboxylic acid in which R is (a) is preferably acetic acid, propionic acid, 2-methylbutanoic acid, pivalic acid, lauric acid, myristic acid, palmitic acid, or stearic acid, and more preferably pivalic acid.

[0062] When R of the carboxylic acid of formula (1) is (b) an alicyclic hydrocarbon group that can be crosslinked or condensed, R is preferably an adamantyl group, a cyclohexyl group, or a 4-(tert-butyl)cyclohexyl group, and more preferably an adamantyl group.

[0063] When R of the carboxylic acid of formula (1) is (c) an oxyalkyl group substituted with an alicyclic hydrocarbon group which can be cross-linked or condensed, R is preferably bornyloxymethyl, isobornyloxymethyl or menthyl.

[0064] When R of the carboxylic acid of formula (1) is (d) a phenoxyalkyl group, a phenoxyalkyl group substituted with an alkyl group, or a phenoxyalkyl group substituted with an alicyclic hydrocarbon group that can be crosslinked or condensed, the alkyl group may be a straight chain or a branched chain. The carbon number of the alkyl group is, for example, 1 to 17, or 1 to 12, 1 to 10, 1 to 6, 1 to 4, 1 to 3, 1 to 2, or 1. R is preferably a phenoxymethyl group, a 4-(tert-butyl)phenoxymethyl group, a 4-(1,1,3,3-tetramethyl)butylphenoxymethyl group, adamantylphenoxymethyl group, a bornylphenoxymethyl group, a bornylphenoxypentyl group, or a menthylphenoxymethyl group, and more preferably a 4-(tert-butyl)phenoxymethyl group, a 4-(1,1,3,3-tetramethyl)butylphenoxymethyl group, adamantylphenoxymethyl group, a bornylphenoxymethyl group, or a menthylphenoxymethyl group.

[0065] ASA may also be a compound composed of a skeleton derived from an olefin which may have a branched chain having 4 to 18 carbon atoms and a succinic anhydride skeleton. Examples of ASA include pentenyl succinic anhydride, hexenyl succinic anhydride, octenyl succinic anhydride, decenyl succinic anhydride, undecenyl succinic anhydride, dodecenyl succinic anhydride, tridecenyl succinic anhydride, tetradecenyl succinic anhydride, hexadecenyl succinic anhydride, octadecenyl succinic anhydride, and isooctadecenyl succinic anhydride. Examples of commercially available ASA include AS1533 (manufactured by Seikyo PMC Co., Ltd.), TNS135 (manufactured by Seikyo PMC Co., Ltd.), Rikacid DDSA (manufactured by Shin Nippon Rika Co., Ltd.; tetrapropylene succinic anhydride (3-dodecenyl succinic anhydride)), DSA (manufactured by Sanyo Chemical Industries, Ltd.), and PDSA-DA (manufactured by Sanyo Chemical Industries, Ltd.).

[0066] The alkyl succinic anhydride may have a structure in which the unsaturated bonds in the alkenyl groups of the above-mentioned various ASAs are reduced by hydrogenation. In other words, the alkyl succinic anhydride may be a succinic anhydride in which the alkenyl groups of ASA are converted into alkyl groups. Examples of the alkyl succinic anhydride are octyl succinic anhydride, dodecyl succinic anhydride, tridecyl succinic anhydride, tetradecyl succinic anhydride, hexadecyl succinic anhydride, and octadecyl succinic anhydride.

[0067] The content of nanofibers in the first resin powder 11 is, for example, 15% by mass or less. The lower limit of the content may be 0.5% by mass or more, 1% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, and further 9% by mass or more. The upper limit of the content may also be 14% by mass or less, 13% by mass or less, 12% by mass or less, and further 11% by mass or less.

[0068] The first resin powder 11 may optionally contain other materials besides homopolymer PP and nanofibers. Examples of other materials are additives. Examples of additives are fillers, compatibilizers, colorants, antistatic agents, heat stabilizers, flame retardants, and antioxidants. Other materials may be organic materials or inorganic materials. However, other materials are not limited to the above examples. When other materials are included, their content in the first resin powder 11 is, for example, less than 10% by mass, or less than 7% by mass, less than 5% by mass, less than 3% by mass, or further less than 1% by mass. The lower limit of the content is, for example, greater than 0.1% by mass, or greater than 0.3% by mass.

[0069] Examples of fillers include talc, carbon, glass, metal, metal oxides, and silicon dioxide. Examples of metal oxides include aluminum oxide and titanium dioxide. The filler may be in the form of fibers, beads, or flakes. Carbon may be carbon fibers. Glass may be glass fibers or glass beads. However, the filler is not limited to the above examples.

[0070] An example of a compatibilizer is a material that improves the dispersibility of the nanofibers in the polypropylene. When the nanofibers are CNFs, an example of such a material is maleic anhydride modified polypropylene (MAPP).

[0071] The average particle size of the first resin powder 11 is, for example, 20 to 80 μm. The lower limit of the average particle size may be 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, or 50 μm or more. The upper limit of the average particle size may be 75 μm or less, 70 μm or less, or 65 μm or less. The average particle size of the resin powder and the powder material can be obtained as D50 based on the volume-based particle size distribution measured by the laser diffraction / scattering method.

[0072] The first resin powder 11 can be formed, for example, by mixing a powder of homopolymer PP with nanofibers. The first resin powder 11 can be formed by forming a resin molded body (e.g., a sheet, a strand, a scale body, etc.) containing homopolymer PP and nanofibers, and then crushing the resin molded body. The resin molded body can be formed, for example, by melt kneading and molding using a twin-screw extruder or the like. The crushing is, for example, freeze crushing. However, the method for forming the first resin powder 11 is not limited to the above example.

[0073] (Second resin powder)

[0074] Block PP is typically a mixture of homopolymer PP or random PP, a copolymer of propylene and other monomers (hereinafter referred to as copolymer A) and a homopolymer of the other monomer. Copolymer A is generally a rubbery substance that does not show crystallinity. A typical example of block PP has a continuous phase mainly comprising homopolymer PP or random PP (preferably homopolymer PP) and a discontinuous phase comprising a homopolymer of copolymer A and other monomers. In the discontinuous phase, copolymer A can cover the homopolymer of other monomers. The mass ratio of the continuous phase to the discontinuous phase is, for example, 60 to 90:40 to 10. Block PP is usually produced by adding other monomers to a system obtained by polymerizing homopolymer PP or to a system in polymerization and further polymerizing. The other monomers are typically olefins. Among them, olefins do not include propylene. Examples of olefins are ethylene, butene and hexene, and may also be ethylene. In other words, copolymer A can be a propylene / ethylene copolymer (typically ethylene-propylene rubber), and block PP can contain a propylene / ethylene copolymer.

[0075] The melting point of the block PP is, for example, 150 to 180°C, preferably 155 to 175°C, and more preferably 160 to 170°C. The recrystallization temperature of the block PP is, for example, 110 to 140°C, preferably 115 to 135°C, and more preferably 120 to 130°C. The difference between the melting point and the recrystallization temperature is preferably 30°C or more, more preferably 35°C or more, further preferably 38°C or more, and particularly preferably 40°C or more. The upper limit of the difference is, for example, 60°C or less. The difference in melting point and recrystallization temperature between the block PP and the homopolymer PP contained in the first resin powder 11 is preferably 15°C or less, more preferably 10°C or less, and further preferably 5°C or less.

[0076] Block PP is generally crystalline. The degree of crystallinity of block PP is, for example, 40 to 70%, preferably 50% or more, based on the homopolymer PP portion contained in the block PP.

[0077] The weight average molecular weight (Mw) of the block PP is, for example, tens of thousands to millions, 500,000 to 3,000,000, or further 500,000 to 2,000,000, based on the homopolymer PP portion contained in the block PP.

[0078] The MFR value of the block PP is, for example, 20 to 60 g / 10 minutes, may be 30 to 50 g / 10 minutes, or further may be 35 to 45 g / 10 minutes.

[0079] The second resin powder 12 may contain one or two or more types of block PP.

[0080] The second resin powder 12 preferably does not contain nanofibers. When containing nanofibers, the content of nanofibers in the second resin powder 12 may be 5 mass % or less, 4 mass % or less, 3 mass % or less, 2 mass % or less, 1 mass % or less, or further 0.5 mass % or less.

[0081] The second resin powder 12 may contain other materials other than block PP. Examples of other materials are the same as those described in the first resin powder 11. When other materials are contained, the content of the other materials in the second resin powder 12 is, for example, 10% by mass or less, or 7% by mass or less, 5% by mass or less, 3% by mass or less, or 1% by mass or less. The lower limit of the content is, for example, 0.1% by mass or more, or 0.3% by mass or more.

[0082] The average particle size of the second resin powder 12 is, for example, 30 to 100 μm. The lower limit of the average particle size may be 35 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, 55 μm or more, or 60 μm or more. The upper limit of the average particle size may be 90 μm or less, 80 μm or less, 75 μm or less, or 70 μm or less.

[0083] The second resin powder 12 can be formed, for example, by forming a resin molded body (e.g., a sheet, a strand, a scale, etc.) containing block PP and pulverizing it. The method of forming the resin molded body and the method of pulverizing it are as described above in the description of the first resin powder 11. However, the method of forming the second resin powder 12 is not limited to the above example.

[0084] (Powder material)

[0085] The content of homopolymer PP in the powder material 1 is, for example, 10 to 60% by mass. The lower limit of the content may be 15% by mass or more, 17% by mass or more, 20% by mass or more, 22% by mass or more, 24% by mass or more, and further 25% by mass or more. The upper limit of the content may be 55% by mass or less, 50% by mass or less, 45% by mass or less, 40% by mass or less, 35% by mass or less, 33% by mass or less, and further 30% by mass or less.

[0086] The content of block PP in the powder material 1 is, for example, 35 to 85% by mass. The lower limit of the content may be 40% by mass or more, 42% by mass or more, 45% by mass or more, 47% by mass or more, 50% by mass or more, 52% by mass or more, 55% by mass or more, 57% by mass or more, 60% by mass or more, 62% by mass or more, and further 65% by mass or more. The upper limit of the content may be 80% by mass or less, 77% by mass or less, 75% by mass or less, 72% by mass or less, and further 70% by mass or less.

[0087] Regarding the powder material 1 , the blending ratio of the second resin powder 12 to the first resin powder 11 can be evaluated, for example, as shown in the following (1) to (4).

[0088] (1) After dispersing the powder material 1 to be evaluated in an uncured epoxy resin, the epoxy resin is cured. It should be noted that, before dispersion, it is confirmed that the powder material 1 to be evaluated contains the first resin powder 11 containing homopolymer PP and nanofibers and the second resin powder 12 containing block PP. This can be confirmed by a known method.

[0089] (2) Observe the cross section of the solidified product using a magnified observation method such as an optical microscope or an electron microscope. The optical microscope may be a fluorescence microscope that can capture the fluorescence that may be emitted by nanofibers such as CNF. The observed area is, for example, area A described below.

[0090] (3) Evaluate the area ratio of the domain mainly containing homo-PP to the domain mainly containing block PP in the magnified observation image. The evaluation can be made by using the visual difference (contrast difference, etc.) between homo-PP and block PP in the magnified observation image. The area of ​​the domain containing nanofibers such as CNF also includes the area of ​​nanofibers.

[0091] (4) Calculate the volume ratio from the area ratio and convert it to a mass ratio. The mass ratio can be converted using the specific gravity of the homopolymer PP and block PP. If the specific gravity is roughly the same, the volume ratio can also be used as the mass ratio.

[0092] The content of nanofibers in the powder material 1 is, for example, 1 to 8% by mass. The lower limit of the content may be 1.5% by mass or more, 2% by mass or more, 2.5% by mass or more, or 3% by mass or more. The upper limit of the content may be 7% by mass or less, 6% by mass or less, 5% by mass or less, 4.5% by mass or less, or 4.0% by mass or less.

[0093] The average particle size of the powder material 1 is, for example, 30 to 80 μm. The lower limit of the average particle size may be 35 μm or more, 40 μm or more, 45 μm or more, or 50 μm or more. The upper limit of the average particle size may be 75 μm or less, 70 μm or less, or 65 μm or less.

[0094] The powder material 1 may contain the first resin powder 11 and / or the second resin powder 12, in particular, fine powder of the first resin powder 11. The degree of containing fine powder can be evaluated by measuring the particle size distribution of the powder material 1 based on the laser diffraction / scattering method. In the powder material 1, in the volume-based particle size distribution measured by the laser diffraction / scattering method, the cumulative frequency A of particles smaller than 38 μm and / or the cumulative frequency B of particles smaller than 30 μm may be 8% or more, or 10% or more, 11% or more, 12% or more, 14% or more, 15% or more, 17% or more, and further 19% or more. The cumulative frequency B may also be 10% or more, 11% or more, 12% or more, 13% or more, and further 14% or more. In addition, in the volume-based particle size distribution measured by the laser diffraction / scattering method, the cumulative frequency C of particles smaller than 20 μm may be 5% or more, or 6% or more, and further 7% or more. It should be noted that fine powders are easy to aggregate, and the aggregation of fine powders in a laser sintering 3D printer may hinder the manufacture of a molded body. However, since nanofibers, especially CNF, show an effect of inhibiting the aggregation of powders, the powder material 1 containing nanofibers is suitable for use in a 3D printer containing fine powders. In the case of focusing on the aggregation inhibition effect, the content of nanofibers in the powder material 1 is preferably 2% by mass or more.

[0095] Since a large amount of fine powder can be contained, for example, the following effects can be expected.

[0096] (1) In order to produce a three-dimensional object, there is no need to remove the fine powder in advance, which can reduce the production cost of the powder material and the molded object. Since the fine powder has a strong adhesion, it takes a lot of time and cost to remove it.

[0097] (2) It can improve the surface smoothness of three-dimensional objects.

[0098] (3) Since the heat capacity of fine powder is small, the scanning speed of the laser can be increased, thereby reducing the time and manufacturing cost required for the production of three-dimensional objects.

[0099] (4) Since the molded product can be molded so that the fine powder can enter the voids between powders having a larger particle size, the proportion of voids contained in the molded product can be reduced, and the mechanical properties of the molded product can be further improved.

[0100] In the powder material 1, coarse powder can be removed. For example, in the volume-based particle size distribution measured by the laser diffraction / scattering method, the cumulative frequency D of particles with a particle size of 115 μm or less can be 85% or more, 85.5% or more, or even 86% or more. Coarse powder can be removed by classification using a sieve, a screen, or the like. The test sieve specified in JIS Z8801: 2006 can be used for classification.

[0101] The powder material 1 may optionally contain other materials other than the first resin powder 11 and the second resin powder 12. Examples of other materials are the same as examples of other materials optionally contained in the first resin powder 11. When other materials are contained, the content of the other materials in the powder material 1 is, for example, 10% by mass or less, and may be 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, and further 3% by mass or less. The lower limit of the content is, for example, 0.3% by mass or more, and may be 0.5% by mass or more, and further 1.0% by mass or more.

[0102] The powder material 1 can also be used for purposes other than the production of three-dimensional objects using a laser sintering 3D printer.

[0103] The powder material 1 can be formed by mixing a first resin powder 11 and a second resin powder 12 , for example.

[0104] [Method for producing three-dimensional objects]

[0105] The manufacturing method of the present invention includes an operation of three-dimensionally molding the powder material of the present invention using a laser sintering 3D printer to obtain a three-dimensional molded object as a polypropylene molded body.

[0106] In a laser sintering 3D printer, a three-dimensional object is typically produced as follows (see Figure 2). The printer 51 includes a preheating tank 52, a molding tank 53, a scraper 54 and a laser irradiation device 55. The bottom plates 58 and 59 of the preheating tank 52 and the molding tank 53 are movable in the up and down directions. The powder material 50 is contained in the preheating tank 52. The powder material 50 is usually preheated to a temperature slightly lower than the melting point of the resin contained in the powder material 50. By preheating, the melting of the powder material based on laser irradiation can be accelerated. Therefore, for example, the scanning speed of the laser can be increased, thereby shortening the molding time. The preheated powder material 50 flows into the molding tank 53 due to the sliding of the scraper 54, and forms a layer of a specified thickness in the molding tank 53. The specified thickness varies depending on the size of the printer 51, etc., and is typically adjusted to about 100 to 300 μm. Then, the layer of the powder material 50 in the molding groove 53 is irradiated with laser 56 from the laser irradiation device 55 to melt the powder material, thereby forming a bonding layer (thermal bonding layer) of the powder material 50 having a predetermined pattern. The inflow of the powder material 50 from the preheating groove 52 to the molding groove 53 and the formation of the bonding layer based on the irradiation of the laser 56 are repeated to shape the three-dimensional molded object. After the formation of the bonding layer, if the next bonding layer is formed before the temperature of the layer drops below the recrystallization temperature, the bonding layers can be more reliably bonded. It should be noted that as the molding proceeds, the bottom plate 58 of the preheating groove 52 rises and the bottom plate 59 of the molding groove 53 falls. The printer 51 is an example of a laser sintering 3D printer. As long as the thermal bonding of the powder material based on laser irradiation is used, the structure and specific operation method of the printer are not limited to the above example. The manufacturing method of the present invention can optionally include any process as long as a three-dimensional molded object can be obtained.

[0107] [Three-dimensional objects]

[0108] An example of the three-dimensional object of the present invention is shown in Figure 3 middle. Figure 3 A cross section of the three-dimensional object 2 is shown in FIG. Figure 3 The three-dimensional object 2 comprises polypropylene. The three-dimensional object 2 comprises a first domain 21 comprising homopolymer PP and nanofibers and a second domain 22 comprising block PP. Figure 3 The first domain 21 and the second domain 22 shown are fused with each other. The three-dimensional object 2 can be manufactured by applying the modeling based on the laser sintering type 3D printer to the powder material 1 of the present invention. In this case, the three-dimensional object 2 is a joint body of the powder material 1 (the first resin powder 11 and the second resin powder 12 contained therein). The first domain 21 comes from the first resin powder 11, and the second domain 22 comes from the second resin powder 12.

[0109] When observing the cross section of the three-dimensional object 2, the ratio of the area occupied by the first domain 21 in the cross section can be 65% or less, 60% or less, 55% or less, 50% or less, 45% or less, 40% or less, 38% or less, 35% or less, and further 33% or less. Its lower limit can be, for example, 22% or more, 25% or more, 27% or more, and further 30% or more. When observing the cross section of the three-dimensional object 2, the ratio of the area occupied by the second domain 22 in the cross section can be 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 62% or more, 65% or more, and further 67% or more. Its upper limit can be, for example, 78% or less, 75% or less, 73% or less, and further 70% or less. In the above cross section, the area occupied by the second domain 22 can be larger than the area occupied by the first domain 21. The cross-section observation can be carried out on a rectangular region A with a long side of about 500 to 1500 μm and a short side of about 400 to 1200 μm on the cross-section. Region A can be a rectangle with a long side of 630 μm and a short side of 460 μm. In the cross-section observation, an optical microscope, an electron microscope or the like can be used for magnified observation. The magnified observation technique can be a fluorescence microscope or a phase contrast microscope. CNF can usually be observed using a fluorescence microscope by using the phenomenon of emitting fluorescence to excitation light in the wavelength range of 400 to 500 nm to distinguish between the first phase domain 21 containing CNF and the second phase domain 22 not containing CNF.

[0110] Figure 3The three-dimensional object 2 shown has a sea-island structure, and the sea-island structure has an island portion based on the first phase domain 21 and a sea portion based on the second phase domain 22. In other words, the three-dimensional object of the present invention may have a cross section in which a sea-island structure having an island portion based on the first phase domain 21 and a sea portion based on the second phase domain 22 is observed. The island portion is a phase (discontinuous phase, dispersed phase) confirmed to be dispersed inside the sea portion as a continuous phase in the cross section in which the sea-island structure is observed. However, in the cross section in which the sea-island structure is observed, there may be a portion in which the second phase domain 22 is dispersed inside the first phase domain 21. In other words, in the cross section, there may be a portion in which the second phase domain 22 is surrounded by the first phase domain 21 connected in a ring shape. In the cross section including the first phase and the second phase, when the sum of the perimeters of the first phase continuously surrounded by the second phase is greater than the sum of the perimeters of the second phase continuously surrounded by the first phase, the second phase may be a continuous phase and the first phase may be a discontinuous phase. The three-dimensional object 2 having a cross section with an island structure is particularly suitable for improving the balance between impact resistance and bending properties. According to the research of the present inventors, when the ratio of the second resin powder 12 to the first resin powder 11 is expressed as the mass of the second resin powder 12 when the mass of the first resin powder 11 is 1, and is 1.4 or more and 3.0 or less, preferably 1.5 or more and 2.1 or less, it is particularly suitable for manufacturing a three-dimensional object 2 having a cross section with an island structure.

[0111] The size of the cross section for observing the presence or absence of the sea-island structure can be expressed as 1.0×10 4 μm 2 Above, 2.5×10 4 μm 2 Above, 5.0×10 4 μm 2 Above, 7.5×10 4 μm 2 Above, 1.0×10 5 μm 2 Above, 2.5×10 5 μm 2 Above, 2.89×10 5 μm 2 Above, 5.0×10 5 μm 2 Above, 1mm 2 Above, 2.5mm 2 Above, further 5mm 2 The upper limit of the size of the observed cross section is, for example, 100 mm in area. 2 Below, 50mm is also possible 2 Below, 25mm 2 Below, further 10mm 2The cross section to be observed may be a rectangle or a square. The cross section to be observed may be the above-mentioned area A. The method for observing the cross section of a three-dimensional object is as described above.

[0112] In the three-dimensional object of the present invention, the cross section having the sea-island structure may exist in any direction. In other words, the three-dimensional object of the present invention may have a sea-island structure that is three-dimensionally developed.

[0113] The average domain diameter of the first domain 21 as the island portion of the sea-island structure is, for example, 20 to 120 μm, or 30 to 100 μm, 40 to 90 μm, or even 50 to 80 μm. The average domain diameter can be obtained as D50 based on the area distribution of the first domain 21 contained in the observed image of the cross section of the three-dimensional object 2, for example, the observed image of the above-mentioned region A. The area distribution can be obtained by image processing of the above-mentioned observed image, and the image processing can be performed using software such as Image J.

[0114] The Charpy impact strength of the three-dimensional object 2 is, for example, 5.5 kJ / m 2 Above, it can also be 5.7kJ / m 2 Above, 6kJ / m 2 Above, 6.5kJ / m 2 Above, 7kJ / m 2 Above, 7.5kJ / m 2 Above, 8kJ / m 2 Above, 8.5kJ / m 2 Above, 9kJ / m 2 Above, 9.4kJ / m 2 Above, 10kJ / m 2 Above, 10.5kJ / m 2 Above, 10.9kJ / m 2 Above, 11kJ / m 2 Above, further 11.5 kJ / m 2 The upper limit of the Charpy impact strength is, for example, 25 kJ / m 2 Herein, the Charpy impact strength is a value obtained as an unnotched Charpy impact strength based on a side impact in accordance with the provisions of JIS K7111-1:2012.

[0115] The bending modulus of the three-dimensional object 2 is, for example, 1.2 GPa or more, and may be 1.24 GPa or more, 1.3 GPa or more, 1.35 GPa or more, 1.4 GPa or more, 1.45 GPa or more, 1.5 GPa or more, 1.55 GPa or more, 1.6 GPa or more, 1.65 GPa or more, and further 1.7 GPa or more. The upper limit of the bending modulus is, for example, 3 GPa or less, and may be 2.5 GPa or less, and further 2 GPa or less. The bending modulus is a value obtained according to the A method (a method for obtaining a bending stress / bending strain curve based on a test speed) specified in JIS K7171:2016.

[0116] The bending strength of the three-dimensional object 2 is, for example, 18 MPa or more, and may be 20 MPa or more, 21 MPa or more, 22 MPa or more, 23 MPa or more, 24 MPa or more, 25 MPa or more, 26 MPa or more, 27 MPa or more, 28 MPa or more, and further 29 MPa or more. The upper limit of the bending strength is, for example, 35 MPa or less, and may be 33 MPa or less, 31 MPa or less, and further 30 MPa or less. The bending strength is a value obtained according to the A method (a method for obtaining a bending stress / bending strain curve based on a test speed) specified in JIS K7171:2016.

[0117] In the three-dimensional shaped object 2, the Charpy impact strength can also be 5.5 kJ / m 2 The above, bending modulus is 1.2 GPa or more.

[0118] In the three-dimensional shaped object 2, the Charpy impact strength can also be 5.5 kJ / m 2 The flexural modulus is 1.2 GPa or more, and the flexural strength is 21 MPa or more. The Charpy impact strength can also be 8.0 kJ / m 2 The above, the bending modulus is 1.7 GPa or more, and the bending strength is 28 MPa or more.

[0119] In the three-dimensional object 2, the Charpy impact strength may be 5.5 kJ / m 2 At the same time, the product of the Charpy impact strength and the flexural modulus is 12.5 GPa·kJ / m 2 Above, it can also be 13.0GPa·kJ / m 2 Above, 15.0GPa·kJ / m 2 Above, 17.0GPa·kJ / m 2 Above, 19.0GPa·kJ / m 2 Above, further 20.0 GPa·kJ / m 2 above.

[0120] The specific gravity of the three-dimensional object 2 is, for example, 0.7 to 0.9 g / cm 3 , can also be 0.75~0.85g / cm 3 , and further 0.75 to 0.8 g / cm 3 .

[0121] Examples of the three-dimensional object 2 are exterior or interior decorative parts for vehicles such as bumpers, door trims, and wheel covers, medical devices such as prosthetic legs, prosthetic hands, and therapeutic devices, electronic components, parts of lighting equipment, sporting goods, and molds (including trial production molds). Vehicles include not only motor vehicles but also rail vehicles. Motor vehicles include electric vehicles. However, the three-dimensional object 2 is not limited to the above examples.

[0122] Example

[0123] Hereinafter, the present invention will be described in further detail using examples. However, the present invention is not limited to the specific embodiments described below.

[0124] (Manufacturing Example 1-1: Preparation of First Resin Powder A1)

[0125] Homopolymer PP pellets (Novatec PP, MA04A, manufactured by Polypro Co., Ltd., Japan, melting point 166°C, recrystallization temperature 124°C, MFR 40g / 10 minutes), CNF manufactured based on the method disclosed in Japanese Patent No. 5638001, and maleic anhydride modified PP (MAPP; H1000P manufactured by Toyobo Co., Ltd.) as a compatibilizer are melt-kneaded using a melt extruder. The conditions of melt kneading are set to be the same in all manufacturing examples. CNF has a fiber diameter ranging from 10 nm to 10 μm, an average fiber length ranging from 10 nm to 100 μm, and an average fiber diameter of less than 1000 nm. In addition, a portion of the CNF is subjected to a surface hydrophobic treatment (acetylation modification) (modified portion) using acetyl groups. Then, the kneaded product is discharged from the extruder to obtain a scaly resin molded body. Then, the obtained resin molded body was freeze-crushed, and then subjected to classification treatment to remove coarse powder, thereby obtaining the first resin powder A1 containing homopolymer PP and CNF. In the classification treatment, a test sieve with a nominal aperture of 106 μm specified in JIS Z8801-1 was used. The classification treatment was performed twice. The classification treatment method was set to be the same in all manufacturing examples. The contents of CNF and MAPP in the first resin powder A1 were both 10.0% by mass.

[0126] (Manufacturing Example 1-2: Preparation of First Resin Powder A2)

[0127] A first resin powder A2 containing homoPP and CNF was obtained in the same manner as in Production Example 1-1 except that the homoPP pellets, CNF and MAPP were melt-kneaded so that the contents of CNF and MAPP in the obtained resin powder were 5.0 mass % and 10.0 mass %, respectively.

[0128] (Manufacturing Example 1-3: Preparation of First Resin Powder A3)

[0129] A first resin powder A3 containing homoPP and CNF was obtained in the same manner as in Production Example 1-1 except that the homoPP pellets, CNF and MAPP were melt-kneaded so that the contents of CNF and MAPP in the obtained resin powder were 15.0 mass % and 17.5 mass %, respectively.

[0130] (Manufacturing Example 1-4: Preparation of First Resin Powder A4)

[0131] A first resin powder A4 containing homopolymer PP and CNF was obtained in the same manner as in Production Example 1-1 except that talc (manufactured by Nippon Talc Co., Ltd., MS-P) was further added to the homopolymer PP pellets, CNF and MAPP for melt kneading. The contents of CNF, MAPP and talc in the first resin powder A4 were 10 mass %, 6.5 mass % and 10.0 mass %, respectively.

[0132] (Manufacturing Example 1-5: Preparation of First Resin Powder A5)

[0133] A first resin powder A5 containing homoPP and CNF was obtained in the same manner as in Production Example 1-1 except that the homoPP pellets, CNF and MAPP were melt-kneaded so that the contents of CNF and MAPP in the obtained resin powder were both 5.0 mass %.

[0134] (Production Example 2-1: Preparation of Second Resin Powder B1)

[0135] Block PP pellets (Prime Polypro J707G manufactured by Prime Polymer Co., Ltd., melting point 165°C, recrystallization temperature 126°C, MFR 30 g / 10 min, other monomer: ethylene) were freeze-ground and then subjected to classification treatment to remove coarse powder to obtain a second resin powder B1 containing block PP.

[0136] (Manufacturing Example 2-2: Preparation of Second Resin Powder B2)

[0137] Block PP particles (Prime Polymer Co., Ltd., Prime Polypro, J707G) and CNF (Nippon Paper Industries, Ltd.) are melt-kneaded using a melt extruder. CNF has a fiber diameter ranging from 10 nm to 10 μm, an average fiber length ranging from 10 nm to 100 μm, and an average fiber diameter of less than 1000 nm, and a portion of the CNF is acetylated (modified portion). Then, the kneaded product is discharged from the extruder to obtain a flaky resin molded body. Then, the obtained resin molded body is freeze-ground, and a classification treatment is performed to remove coarse powder to obtain a second resin powder B2 containing block PP. The content of CNF in the second resin powder B2 is 5.0% by mass.

[0138] (Manufacturing Example 2-3: Preparation of Second Resin Powder B3)

[0139] Homopolymer PP pellets (Novatec PP, MA04A manufactured by Polypro Co., Ltd., Japan) and CNF manufactured by the method disclosed in Japanese Patent No. 5496435 are melt-kneaded using a melt extruder. CNF has a fiber diameter ranging from 10 nm to 10 μm, an average fiber length ranging from 10 nm to 100 μm, and an average fiber diameter of less than 1000 nm, and a portion of the CNF is hydrophobized (ASA modified) (modified portion) using hexadecene succinic anhydride (T-NS135 manufactured by Starlight PMC Co., Ltd.), which is one type of alkenyl succinic anhydride (ASA). Then, the kneaded product is discharged from the extruder to obtain a scaly resin molded body. Then, the obtained resin molded body is freeze-crushed, and a classification treatment to remove coarse powder is performed to obtain a resin powder P. The content of homopolymer PP in the obtained resin powder P is 50.0% by mass, and the content of CNF is 31.0% by mass. Then, the obtained resin powder P was diluted with the resin powder R2 of block PP prepared in Production Example 5-2 to obtain the second resin powder B3 containing block PP. The content of block PP in the second resin powder B3 was 83.8% by mass, the content of homopolymer PP was 8.1% by mass, and the content of CNF was 5.0% by mass.

[0140] The compositions of the first resin powder and the second resin powder produced in Production Examples 1-1 to 1-5 and Production Examples 2-1 to 2-3 are summarized in Table 1 below.

[0141] [Table 1]

[0142]

[0143] (Manufacturing Examples 3-1 to 3-9: Preparation of Powder Materials C1 to C9)

[0144] The first resin powder and the second resin powder produced in Production Examples 1-1 to 1-5 and Production Examples 2-1 to 2-3 were mixed at the blending ratios shown in the following Table 2 to obtain powder materials C1 to C9.

[0145] [Table 2]

[0146]

[0147] The compositions of powder materials C1 to C9 are shown in Table 3 below.

[0148] [Table 3]

[0149]

[0150] (Manufacturing Example 4-1: Preparation of Powder Material D1)

[0151] The resin powder P prepared in Manufacturing Example 2-3 is diluted with the resin powder R2 of the block PP prepared in Manufacturing Example 5-2 so that the CNF content is 10.0% by mass, and then melt-kneaded using a melt extruder. Then, the kneaded product is discharged from the extruder to obtain a flaky resin molded body. Then, the obtained resin molded body is freeze-ground, and then a classification treatment is performed to remove coarse powder to obtain a powder material D1 composed of 1 resin powder. The composition of the powder material D1 is homopolymer PP / CNF / modified part / block PP = 16.2% by mass / 10.0% by mass / 6.0% by mass / 67.8% by mass.

[0152] (Manufacturing Example 4-2: Preparation of Powder Material D2)

[0153] Resin powder Q was obtained in the same manner as in Manufacturing Example 1-1, except that the particles of homo-PP, CNF and MAPP were melt-kneaded so that the contents of CNF and MAPP in the obtained resin powder were both 30.0% by mass. Then, resin powder Q was diluted with resin powder R1 of homo-PP prepared in Manufacturing Example 5-1 so that the content of CNF was 5% by mass, and then melt-kneaded using a melt extruder. Then, the kneaded product was discharged from the extruder to obtain a scaly resin molded body. Then, the obtained resin molded body was freeze-pulverized, and then a classification treatment was performed to remove coarse powder to obtain a powder material D2 composed of one resin powder. The composition of powder material D2 is homo-PP / CNF / MAPP / modified part = 88.7% by mass / 5.0% by mass / 5.0% by mass / 1.3% by mass.

[0154] (Manufacturing Example 4-3: Preparation of powder material D3)

[0155] Powder material D3 composed of one resin powder was obtained in the same manner as in Production Example 4-2 except that resin powder P prepared in Production Example 2-3 was used instead of resin powder Q. The composition of powder material D3 was homopolymer PP / CNF / modified part = 91.9 mass % / 5.0 mass % / 3.1 mass %.

[0156] (Manufacturing Example 5-1: Preparation of Powder Material R1)

[0157] Homopolymer PP pellets (Novatec PP, MA04A manufactured by Polypro Japan Co., Ltd.) were melt-kneaded using a melt extruder. The kneaded product was then discharged from the extruder to obtain a flaky resin molded body. The obtained resin molded body was then freeze-ground and subjected to classification treatment to remove coarse powder, thereby obtaining a powder material R1 composed of a homopolymer PP resin powder.

[0158] (Manufacturing Example 5-2: Preparation of Powder Material R2)

[0159] Block PP pellets (Prime Polypro, J707G, manufactured by Prime Polymer Co., Ltd.) were melt-kneaded using a melt extruder. The kneaded product was then discharged from the extruder to obtain a flaky resin molded body. The obtained resin molded body was then freeze-ground and subjected to classification treatment to remove coarse powder, thereby obtaining a powder material R2 consisting of a block PP resin powder.

[0160] (Examples 1 to 12, Comparative Examples 1 to 3, Reference Examples 1, 2)

[0161] Each powder material prepared as described above was three-dimensionally molded using a laser sintering 3D printer to produce a rectangular parallelepiped test piece (width 10 mm×length 80 mm×thickness 4 mm). The conditions for the three-dimensional molding are as follows.

[0162] Laser type: CO2 laser

[0163] Laser wavelength: 10.6μm

[0164] Laser output power: 30W or 40W

[0165] Laser scanning speed: 5m / s

[0166] Stack thickness (bonding layer thickness): 100μm, 120μm or 150μm

[0167] The mechanical properties (Charpy impact strength, flexural modulus, and flexural strength) of the prepared test pieces were evaluated as follows.

[0168] [Charpy impact strength]

[0169] The Charpy impact strength of the test piece is evaluated as the unnotched Charpy impact strength based on lateral impact in accordance with the provisions of JIS K7111-1:2012. The testing machine used is CHARPACK45C manufactured by Yonekura Manufacturing Co., Ltd. The distance between the fulcrums, the impact velocity, and the nominal pendulum energy are 62 mm, 2.88 m / sec, and 3.99 J, respectively. The measurement temperature is set to 25°C, and the measurement humidity is set to 50% RH. 10 test pieces are evaluated, and the average value is set as the Charpy impact strength of the test piece.

[0170] [Flexural modulus and flexural strength]

[0171] The bending modulus and bending strength are evaluated according to the A method specified in JIS K7171:2016. The test machine used is TENSILON UCT-30T manufactured by ORIENTEC. The distance between the fulcrums is set to 64 mm, and the test speed is set to 2 mm / min. The measurement temperature is set to 25°C, and the measurement humidity is set to 50% RH. Five test pieces are evaluated, and the average value is set as the bending modulus and bending strength of the test piece. The load is applied in the direction corresponding to the direction of the laser irradiation during the three-dimensional modeling of the test piece.

[0172] [proportion]

[0173] The specific gravity was calculated from the volume and mass of the prepared test piece.

[0174] The powder materials used, the conditions for three-dimensional modeling, and the evaluation results of the properties of the examples and comparative examples are shown in Table 4 below. In addition, the magnified observation images of the cross-sections of the three-dimensional models produced in Example 3 and Comparative Example 1 obtained by fluorescence microscopy are shown in Table 4, respectively. Figure 4 and Figure 5 It should be noted that Figure 4 and Figure 5 The image shown is an enlarged observation image when the cross section is irradiated with excitation light of a wavelength at which CNF emits fluorescence. The phase containing CNF is displayed brighter than the phase not containing CNF. For the examples, comparative examples and reference examples, the relationship between the content of block PP in the powder material used and the Charpy impact strength is shown in Figure 6 middle.

[0175] [Table 4]

[0176]

[0177] As shown in Table 1, the three-dimensional shaped objects of the examples showed Charpy impact strength that could not be achieved when using a powder material composed of a homopolymer PP resin powder (Reference Example 1), and showed high bending properties, especially bending elastic modulus. Figure 4 The cross section of the three-dimensional object of Example 3 shown in FIG. 1 has a sea-island structure having an island portion based on a first phase domain containing homopolymer PP and CNF and a sea portion based on a second phase domain containing block PP. Figure 5 As shown in FIG. 1 , the three-dimensional object of Comparative Example 1 formed using a powder material including homopolymer PP, block PP and CNF but composed of one type of resin powder has only one phase. Figure 5 In the magnified observation image, the darker portion is a gap.

[0178] Industrial Applicability

[0179] The powder material for three-dimensional modeling of the present invention can be used in the same applications as conventional powder materials for three-dimensional modeling.

Claims

1. A powder material for three-dimensional modeling, comprising: A first resin powder comprising homopolypropylene and nanofibers, and A second resin powder comprising block polypropylene.

2. The powder material for three-dimensional modeling according to claim 1, wherein: The blending ratio of the second resin powder to the first resin powder is 0.6 or more and 4.0 or less, expressed as the mass of the second resin powder when the mass of the first resin powder is set to 1.

3. The powder material for three-dimensional modeling according to claim 1, wherein: The blending ratio of the second resin powder to the first resin powder is 1.4 or more and 3.0 or less, expressed as the mass of the second resin powder when the mass of the first resin powder is set to 1.

4. The powder material for three-dimensional modeling according to claim 1, wherein: The content of the nanofibers in the first resin powder is 15% by mass or less.

5. The powder material for three-dimensional modeling according to claim 1, wherein: The nanofibers are cellulose nanofibers.

6. The powder material for three-dimensional modeling according to claim 1, wherein: The block polypropylene comprises a copolymer of propylene and an olefin, wherein the olefin does not include propylene.

7. A method for manufacturing a three-dimensional object, the method comprising the step of three-dimensionally molding the powder material for three-dimensional modeling according to any one of claims 1 to 6 using a laser sintering 3D printer to obtain a three-dimensional object.

8. A three-dimensional object comprising polypropylene, The three-dimensional object has: A first phase domain comprising homopolypropylene and nanofibers, and The second phase domain comprises block polypropylene. 9 . The three-dimensional object according to claim 8 , having a cross section in which a sea-island structure is observed, wherein the sea-island structure has an island portion based on the first phase domain and a sea portion based on the second phase domain.

10. The three-dimensional object according to claim 8, wherein the unnotched Charpy impact strength based on lateral impact evaluated in accordance with the provisions of JIS K7111-1:2012 is 5.5 kJ / m 2 above, The flexural modulus evaluated according to the A method specified in JIS K7171:2016 is 1.2 GPa or more. 11 . The three-dimensional object according to claim 10 , wherein the flexural strength evaluated by method A specified in JIS K7171:2016 is 21 MPa or more.

Citation Information

Patent Citations

  • Continuously pickling method for steel sections

    JP1979096435A

  • Light distribution circuit

    JP1981038001A

  • Thermoplastic resin composition and its injection molded article

    JP2002012718A